(untitled) (Open Academia: Journal of Scholarly Research, 2024)
This article explores the complex interplay between the structure of a text highlighting their significance in the translation process. The author addresses the difficulties translators encounter in preserving the stylistic and contextual subtleties of the original work. The article also reviews different translation theories and strategies that lead to these issues, including functional approaches and dynamic equivalence